Rethinking Global Citizenship through Open Science. The Challange of Game-Based Collaborative Research with Young People - Gloria Braga-Blanco; Aquilina Fueyo-Gutiérrez; Santiago Fano-Méndez; Cristina Valdés-Argüelles (Revista Latinoamericana de Tecnología Educativa)
A participatory research process, framed within the paradigm of open science, was undertaken to explore how young people understand and engage with global citizenship in the context of the current severe socio-ecological crisis. Through a co-design methodology, the collaborative game Global Quest was conceived simultaneously as a citizen science research tool and as an open educational resource, inspired by ludopedagogical principles and made available to education professionals for working on global citizenship themes. The game was implemented on 15 occasions with approximately 400 participants, including adolescents and professionals in socio-educational intervention. Qualitative observations collected through structured guides enabled the refinement of the game’s tasks, improving the balance between local and global themes as well as between reflective and expressive activities. Analysis of the collected observations showed that the game facilitates the expression of youth perspectives on participation, diversity, sustainability, and rights, promotes critical reflection on global citizenship, and fosters inclusive collaborative dynamics. The process confirmed the high potential of the game as both a pedagogical and research tool, and its suitability as a participation strategy for creatively addressing social challenges. In addition, the game materials, the accompanying manual, and a didactic guide offering methodological guidelines for its implementation across diverse educational contexts have been developed and openly shared.